Phosphorus Nutrition in Songpu Mirror Carp (Cyprinus carpio Songpu) During Chronic Carbonate Alkalinity Stress: Effects on Growth, Intestinal Immunity, Physical Barrier Function, and Intestinal Microflora - Fan, Ze; Wu, Di; Li, Jinnan; Li, Chenhui; Zheng, Xianhu; Wang, Liansheng (Frontiers in Immunology, 2022)
Carbonate alkalinity is a major environmental stress factor affecting aquatic feed configuration, which easily caused the oxidative stress and hypoimmunity for fish. Hence, the study aimed to assess the potential effect of phosphorus on growth, intestinal oxidation resistance, physical barrier function and microflora for Songpu mirror carp (Cyprinus carpio songpu) (intial average weight of 2.95±0.21 g) reared at the high-concentration carbonate alkalinity environment. A two-factor, three level (2×3) design was applied, in which diets with three different phosphorus levels (3.6, 7.0 and 10.5 g/kg dry matter) were randomly assigned to 0 and 15 mmol/L carbonate alkalinity groups with three replicate aquaria for 8 weeks. Results revealed that weight gain rate (WGR), specific growth rate (SGR), protein efficiency ratio (PER), lipase and amylase activities in intestine significantly (p<0.05) decreased with increasing carbonate alkalinity. A carbonate alkalinity of 15 mmol/L significantly reduced glutathione peroxidase (GSHPx) activities in intestine (p<0.05). The relative expressions of nuclear factor (erythroid-derived 2)-like 2 (Nrf2), GPX1a, Clautin3, Clautin11 and tumour necrosis factor β (TNF-β) in intestine were significantly down-regulated with increasing carbonate alkalinity levels (p<0.05), whereas the relative expressions of interleukin 1β (IL-1β) and tumor necrosis factor (TNF-α) in intestine were significantly up-regulated (p<0.05). At the 15 mmol/L carbonate alkalinity, Songpu mirror carp suffer from hypoimmunity status with failed digestion, antioxidant, inflammation and immune response, thereby inducing the impaired growth. Additionally, significant increments in the abundance of Proteobacteria and significant decrease in the abundance of Fusobacteria and the ratio of Firmicutes/Bacteroidetes were caused by excessively high carbonate alkalinity (15 mmol/L) and excessively low dietary phosphorus supply (3.6 g/kg). Collectively, 7.0 g/kg dietary phosphorus supplementation was effective in promoting intestinal antioxidant enzyme activities and the corresponding gene expression via the Keap1-Nrf2 signaling pathway and in enhancing intestinal immunity by upregulating anti-inflammatory and downregulating pro-inflammatory genes. Appropriate dietary phosphorus supply could promote the formation of beneficial microflora in fresh water, and it has a potential ability to remit the adverse effect of carbonate alkalinity stress on structural composition of intestinal microflora. Hence, consideration should be given to suitable phosphorus supply for fish under the chronic carbonate alkalinity stress.